SEVERAL EVALUATION AND ANALYTICAL INDICATORS OF REGIONAL AUTONOMY IMPLEMENTATION IMPACTS IN INDONESIA: ENERGY AND MINERAL RESOURCE SECTOR DEVELOPMENT - UKAR W. SOELISTIJO (Indonesian Mining Journal, 2012)
In general, the example of case study of the energy and mining company such as PT Bukit Asam (Tbk) in South Sumatera Province and PT INCO (Tbk) in South Sulawesi Province has positive impact to the regional economy in terms of the community development and economic productivity. Coordination between central and regional governments should set up grand strategy of increasing their in- tensive exploration program to identify the distribution, locality, quality and quantity of their energy and mineral resources in every region to develop its potentials and its mineral base downstream industries so instrumental to development in the near future, especially if they have resource endowments having optimal added value and positive terms of trade (TOT) or TOT greater than 1. In overall, it indicates that the energy and mineral resources (EMR) sector could be used as one of among the catalysts to achieve interregional convergence through “cross fertilization” toward the national Gross Domestic Product (GDP) per capita index. All in one purpose is to set up of creating job and income toward a welfare society.